Effect of offering different levels of support and free nicotine replacement therapy via an English national telephone quitline: randomised controlled trial. (23rd March 2012) - Ferguson, Janet; Docherty, Graeme; Bauld, Linda; Lewis, Sarah; Lorgelly, Paula; Boyd, Kathleen Anne; McEwen, Andy; Coleman, Tim
Abstract : Objective To compare the effects of free nicotine replacement therapy or proactive telephone counselling in addition to standard smoking cessation support offered through a telephone quitline. Design Parallel group, 2×2 factorial, randomised controlled trial. Setting National quitline, England. Participants 2591 non-pregnant smokers aged 16 or more residing in England who called the quitline between February 2009 and February 2010 and agreed to set a quit date: 648 were each randomised to standard support, proactive support, or proactive support with nicotine replacement therapy, and 647 were randomised to standard support with nicotine replacement therapy. Interventions Two interventions were offered in addition to standard support: six weeks' nicotine replacement therapy, provided free, and proactive counselling sessions (repeat telephone calls from, and interaction with, cessation advisors). Main outcome measures The primary outcome was self reported smoking cessation for six or more months after the quit date. The secondary outcome was cessation validated by exhaled carbon monoxide measured at six or more months. Results At six months, 17.7% (n=229) of those offered nicotine replacement therapy reported smoking cessation compared with 20.1% (n=261) not offered such therapy (odds ratio 0.85, 95% confidence interval 0.70 to 1.04), and 18.2% (n=236) offered proactive counselling reported smoking cessation compared with 19.6% (n=254) offered standard support (0.91, 0.75 to 1.11). Data validated by carbon monoxide readings changed the findings for nicotine replacement therapy only, with smoking cessation validated in 6.6% (85/1295) of those offered nicotine replacement therapy compared with 9.4% (122/1296) not offered such therapy (0.67, 0.50 to 0.90). Conclusions Offering free nicotine replacement therapy or additional (proactive) counselling to standard helpline support had no additional effect on smoking cessation. Trial registration ClinicalTrials.gov NCT00775944 .